Dynamics of endogenous cytokinin pools in tobacco seedlings: a modelling approach - Lexa, Matej; Genkov, Todor; Malbeck, Jirí; Machácková, Ivana; Brzobohatý, Bretislav (Annals of botany, 2003)
Recent advances in cytokinin analysis have made it possible to measure the content of 22 cytokinin metabolites in the tissue of developing tobacco seedlings. Individual types of cytokinins in plants are interconverted to their respective forms by several enzymatic activities (5'-AMP-isopentenyltransferase, adenosine nucleosidase, 5'-nucleotidase, adenosine phosphorylase, adenosine kinase, trans-hydroxylase, zeatin reductase, beta-glucosidase, O-glucosyl transferase, N-glucosyl transferase, cytokinin oxidase). This paper reports modelling and measuring of the dynamics of endogenous cytokinins in tobacco plants grown on media supplemented with isopentenyl adenine (IP), zeatin (Z) and dihydrozeatin riboside (DHZR). Differences in phenotypes generated by the three cytokinins are shown and discussed, and the assumption that substrate concentration drives enzyme kinetics underpinned the construction of a simple mathematical model of cytokinin metabolism in developing seedlings. The model was tested on data obtained from liquid chromatography/tandem mass spectrometry cytokinin measurements on tobacco seedlings grown on Murashige and Skoog agar nutrient medium, and on plants grown in the presence of IP, Z and DHZR. A close match was found between measured and simulated data, especially after a series of iterative parameter searches, in which the parameters were set to obtain the best fit with one of the data sets.
Keywords: Models, Biological; zeatin; Adenine; Seedlings; fenotyp; cytokininy; metoda Monte Carlo; biologické modely; Cytokinins; tabák; Nicotiana; semenáček; Zeatin; adenin; Phenotype; Monte Carlo Method